Woody bioenergy crop selection can have large effects on water yield: A southeastern United States case study. (October 2018) - Caldwell, P.V.; Jackson, C.R.; Miniat, C.F.; Younger, S.E.; Vining, J.A.; McDonnell, J.J.; Aubrey, D.P.
Abstract: Short-rotation woody crops in the southeastern United States will make a significant contribution to the growing renewable energy supply over the 21st century; however, there are few studies that investigate how species selection may affect water yield. Here we assessed the impact of species selection on annual and seasonal water budgets in unvegetated plots and late-rotation 14–15-year-old intensively managed loblolly pine ( Pinus taeda L.) and sweetgum ( Liquidambar styraciflua L.) stands in South Carolina USA. We found that while annual aboveground net primary productivity and bioenergy produced was similar between species, sweetgum transpiration was 53% higher than loblolly pine annually and 92% greater during the growing season. Canopy interception was 10.5% of annual precipitation and was not significantly different between the two species. Soil evaporation was less than 1.3% of annual precipitation and did not differ between species, but was 26% of precipitation in unvegetated plots. Annual water yield was 69% lower for sweetgum than loblolly pine, with water yield to precipitation ratios of 0.13 and 0.39 for sweetgum and loblolly pine, respectively. If planted at a large scale, the high transpiration and low water yield in sweetgum could result in declines in downstream water availability relative to loblolly pine by the end of the growing season when storage in groundwater, streams, and water supply reservoirs are typically at their lowest. Our results suggest that species selection is of critical importance when establishing forest plantations for woody bioenergy production due to potential impacts on downstream water yield. Highlights: Sweetgum used more water than loblolly pine to produce similar biomass and bioenergy. Sweetgum water yield was lower than loblolly pine, especially in the growing season. Woody biomass species selection may have large implications for water availability.